Becoming Zoö-curious: Reading Sexual Differences in the Field of Animal Life - Rother, Adeline (Humanimalia, 2017)
This paper puts forth a new terminology and rationale for thinking about what it calls the zoö-curious gender discourse. Participants in this discourse are rethinking the sexes, sexualities, and sexual practices of human beings by looking closely at the sex lives of animals, especially insects. Within this strange tradition, I locate the insect metaphors of Jacques Derrida and of other French and francophone such as André Gide, Maurice Maeterlinck, and Jules Michelet. The strange erotic entomology of these French-language writers leads me to a reflection on how the sexual differences of animals play into conceptions of the man-animal difference at large.